Association between onset age and mortality gradients in advanced cardiovascular–kidney–metabolic syndrome - Dai, Jinjin; Wu, Chuanchang; Liu, Shihua; Chen, Shuohua; Hong, Xiaodan; Zhang, Pengyue; Cui, Liufu; Wu, Shouling; Zhang, Zhenhua (Frontiers in Endocrinology, 2025)
IntroductionAdvanced cardiovascular–kidney–metabolic (A-CKM) syndrome portends severe prognosis, but how onset age affects mortality risk remains unquantified.MethodsThis study analyzed 179,328 participants from the Kailuan cohort in Tangshan, China (2006–2022). Using weighted Cox models and stratified analyses, we assessed the association of age at onset with all-cause mortality risk.ResultsAmong 17,283 incident A-CKM cases matched to age-stratified controls, early-onset patients (<45 y) had the highest relative mortality risk (HR = 3.35), which was amplified by smoking (HR = 5.27) and inflammation (hsCRP≥3mg/L: HR = 10.15); midlife onset (45– 54 y) represented the optimal prevention window (NNT = 15), yet with extreme female vulnerability (Stage 4 HR=14.25 vs. male HR=2.54); late-adulthood onset (55–64y) incurred peak absolute burden (ΔRate +8.61/1000PY), while elderly cases (≥65 y) had an attenuated attributable impact despite higher mortality (33.95 vs. 2.48/1000 PY).DiscussionThese findings support an age-stratified management framework: core age phased priorities (risk containment <45 y, preventive interception 45 – 54 y, complication management 55 – 64 y, and renoprotective optimization ≥65 y) augmented by sex-specific refinements—aggressive inflammation control in young men and intensified midlife monitoring for women—resolving the efficiency-burden paradox through calibrated implementation.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=8050, identifier ChiCTR-TNRC-11001489.